1976
DOI: 10.1289/ehp.761351
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation of experimental data from animals to man.

Abstract: Conditions for extrapolating toxicologic data from animals to man were studied. In the search for general regularities associated with the comparative sensitivity of humans and various species of animals to toxins, it was shown that the toxicity parameters of compounds and the biological constants of mammals correlate with body weight. This relationship is well described by a rectilinear regression equation which holds for more than 100 of the most diverse mammalian biological constants. The toxicity parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Hence, intake of high quantities (mg) of 8PN is possible. Pharmacologists claim that doses per kg/BW applied to rats must be 10-15-fold higher than in man in order to exert equipotent effects (Krasovskii 1976, Davidson et al 1986, Vocci & Farber 1988. Hence, the dose used in the present experiments may well be of importance for human physiology and -in agreement with earlier reports (Milligan et al 2000) -may have adverse effects in the uterus that require addition of a progestin to prevent endometrial hyperplasia and carcinoma (Lethaby et al 2004).…”
Section: Discussionsupporting
confidence: 84%
“…Hence, intake of high quantities (mg) of 8PN is possible. Pharmacologists claim that doses per kg/BW applied to rats must be 10-15-fold higher than in man in order to exert equipotent effects (Krasovskii 1976, Davidson et al 1986, Vocci & Farber 1988. Hence, the dose used in the present experiments may well be of importance for human physiology and -in agreement with earlier reports (Milligan et al 2000) -may have adverse effects in the uterus that require addition of a progestin to prevent endometrial hyperplasia and carcinoma (Lethaby et al 2004).…”
Section: Discussionsupporting
confidence: 84%
“…In order to improve the scientific base for extrapolation of laboratory animal data to man, R. L. Dixon (National Institute of Environmental Health Sciences) and G. N. Krasovskii (A. N. Sysin Institute of General and Communal Hygiene) undertook a joint effort aimed at understanding strain and species differences between biological organisms with regard to toxicological response. Soviet scientists have shown that the toxicity parameters of compounds and the biological constants of mammals correlate with body weight and other biological parameters enabling the development of a computational method for extrapolating toxicologic data from animals to the "average" man (25).…”
Section: Problem Area 2 Development Of Methods For Predicting the Biomentioning
confidence: 99%
“…An important corollary of this argument is that behavioral changes may precede histopathological or morphological changes in nerve tissue and thereby prove to be a highly sensitive component in toxicological evaluations. In fact, many countries, most notably the Soviet Union, have relied heavily upon behavioral tests in their toxicology testing for several years, and it is relevant to this point that the acceptable limits of many toxic substances in the Soviet Union are below those established in this country (8,9). This kind of precedent has stimulated the use of behavioral toxicological testing in the United States, with the subsequent reduction of acceptable limits for chemicals such as trichloroethylene (5).…”
Section: Evolution Of Behavioral Toxicologymentioning
confidence: 99%
“…Another organismal variable is the age of the subject. Developing organisms and older, senescent animals differ from the mature adult in their sensitivities to chemicals (8). Unless the research program is specifically aimed at elucidating the effects of chemicals in the developing animal or in older animals, mature adult organisms should be considered as the normative population.…”
Section: Animal Modelsmentioning
confidence: 99%